Mechanisms by which kidney-tonifying Chinese herbs inhibit osteoclastogenesis: Emphasis on immune cells - Jiao, Yi; Wang, Xing; Wang, Qiong; Geng, Qishun; Cao, Xiaoxue; Zhang, Mengxiao; Zhao, Lu; Deng, Tingting; Xu, Yuan; Xiao, Cheng (Frontiers in Pharmacology, 2023)
The immune system plays a crucial role in regulating osteoclast formation and function and has significance for the occurrence and development of immune-mediated bone diseases. Kidney-tonifying Chinese herbs, the Chinese herbal medicine based on the theory of traditional Chinese medicine (TCM) to unify the kidney and strengthen the bone, have been widely used in the prevention and treatment of bone diseases. The common herbs are tonifying kidney-yang and nourishing kidney-yin herbs, which are divided into two parts: one is the compound prescription of TCM, and the other is the single preparation of TCM and its active ingredients. These herbs regulate osteoclastogenesis directly and indirectly by immune cells, however, we have limited information on the differences between the two herbs in osteoimmunology. In this review, the mechanism by which kidney-tonifying Chinese herbs inhibit osteoclastogenesis was investigated, emphasizing the immune response. The differences in the mechanism of action between tonifying kidney-yang herbs and nourishing kidney-yin herbs were analysed, and the therapeutic value for immune-mediated bone diseases was evaluated.